HAMBATAN PELAKSANAAN PENYELESAIAN MALPRAKTIK MEDIK ANTARA HEALTH CARE PROVIDER DENGAN HEALTH CARE RECEIVER MELALUI MEKANISME MEDIASI DI RUMAH SAKIT PURI KAWAN SEJAHTERA DI DENPASAR - Krisma Agus Trimitha, Kadek; Ariawan, I Gusti Ketut (Kertha Semaya : Journal Ilmu Hukum; Vol. 02, No. 01, Februari 2014, 2014)
The relationship between doctor and patient is a relationship that has special status. The doctor or hospital that is located as a party providing health services (Health Care Provider) and the patient as the party receiving health services ( Health Care Receiver). The actual position of the doctor / hospital with the patient is a balanced position ( horizontal ), but in its development began to shift toward the position that contractual vertical position. The shift is exactly what often result in medical disputes, known as Medical malpractice. Malpractice also occurs in Puri Kawan Sejahtera Hospital. Medical malpractice settled in court and out of court. One form of settlement out of court is mediation . In the implementation of the medical service at the Hospital Puri Kawan Sejahtera Malprakit not rare, in which the settlement resolved through mediation. Implementation of mediation is not uncommon to experience barriers implementation. This paper aims to grasp and understand the barriers to the implementation of the Medical malpractice settlement between Health Care Provider Health Care Receiver through mediation mechanism Guys Hospital Welfare. This type of research in this paper is by using the method of empirical jurisdiction. This is a descriptive study (depiction). This study describes the barriers to medical malpractice settlement between Health Care Provider Health Care Reciver with through mediation. Barriers to implementation of mediation in resolving malpractice among Health Care Health Care Provider with Reciver by using mediation, there are two obstacles from within (internal) and external factors (external)
Keywords: Mediation , Medical malpractice , Hospital Welfare Puri Kawan